Pressure-Induced Endocytic Degradation of the Saccharomyces cerevisiae Low-Affinity Tryptophan Permease Tat1 Is Mediated by Rsp5 Ubiquitin Ligase and Functionally Redundant PPxY Motif Proteins - Suzuki, Asaha (American Society for Microbiology, 2013)
Cells of Saccharomyces cerevisiae express two tryptophan permeases, Tat1 and Tat2, which have different characteristics in terms of their affinity for tryptophan and intracellular localization. Although the high-affinity permease Tat2 has been well documented in terms of its ubiquitin-dependent degradation, the low-affinity permease Tat1 has not yet been characterized fully. Here we show that a high hydrostatic pressure of 25 MPa triggers a degradation of Tat1 which depends on Rsp5 ubiquitin ligase and the EH domain-containing protein End3. Tat1 was resistant to a 3-h cycloheximide treatment, suggesting that it is highly stable under normal growth conditions. The ubiquitination of Tat1 most likely occurs at N-terminal lysines 29 and 31. Simultaneous substitution of arginine for the two lysines prevented Tat1 degradation, but substitution of either of them alone did not, indicating that the roles of lysines 29 and 31 are redundant. When cells were exposed to high pressure, Tat1-GFP was completely lost from the plasma membrane, while substantial amounts of Tat1(K29R-K31R)-GFP remained. The HPG1-1 (Rsp5(P514T)) and rsp5-ww3 mutations stabilized Tat1 under high pressure, but any one of the rsp5-ww1, rsp5-ww2, and bul1Δ bul2Δ mutations or single deletions of genes encoding arrestin-related trafficking adaptors did not. However, simultaneous loss of 9-arrestins and Bul1/Bul2 prevented Tat1 degradation at 25 MPa. The results suggest that multiple PPxY motif proteins share some essential roles in regulating Tat1 ubiquitination in response to high hydrostatic pressure.